System Dynamic Simulation of Salacca-Pondoh’s Business as Usual Condition in Sleman District, Yogyakarta Province, Indonesia - Mohammad Prasanto Bimantio (Institute of Research and Community Outreach - Petra Christian University, 2019)
Production of horticultural crops in Sleman District is dominated by salacca-pondoh with total production in 2016 reaching 73 kton, cover up to 98% of total salacca-pondoh’s production in Yogyakarta Province. But salacca-pondoh’s farmers actually got very low-price during harvest season and they only act as a price taker that had low bargaining position, so that their welfare. This research formulated salacca-pondoh’s business as usual condition in Sleman District in form of system dynamic simulation. The factors influenced the low income of farmers during harvest season were identified. Result showed there are several seasonal “pitfalls” points in the farmer’s income which made it dropped far below the average value. It has potential to make the farmers not to replant salacca-pondoh then switch to other fruits that are more profitable. Product diversification either vertically or horizontally by allocating some of the fruit and waste to be convert into derivative products can be a step to increase the income of salacca-pondoh’s farmers and intensify the economic activity in Sleman District.